Effects of body weight-supported treadmill training with or without electrical stimulation on functional ambulation in patients with spinal cord injury: A systematic review and meta-analysis - Zeb, Amir; Mehmood, Beenish; Shah, Arif; Rehman, Shakil ur (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2025)
Earlier studies on body-weight supported treadmill training (BWSTT) for spinal cord injury (SCI) show potential benefits, particularly in improving locomotor function. However, most evidence comes from small studies, necessitating a systematic review to assess its overall impact and acceptability. This review aims to investigate and quantitatively synthesize evidence on the impact of BWSTT, with or without electrical stimulation (FES/ES), on ambulation in individuals with incomplete spinal cord injuries (iSCI) compared to overground gait training or traditional physiotherapy.A bibliographic extensive search for clinical trials involving adults with traumatic spinal cord injury (TSCI) lesions (AISA impairment scale of B, C or D) that compared BWSTT with or without electrical stimulation with overground gait training or traditional physiotherapy was conducted. The end results were walking functionality (walking speed and capacity) and functional independence. BWSTT with FES/ES was analyzed independently, and trial-by-trial data were combined to calculate the mean across group differences via a model with random/fixed effects.Twelve randomized controlled trials (RCTs) were included for qualitative synthesis, whereas nine studies were analyzed for quantitative data. BWSTT as locomotor approach for individual with incomplete SCI did not significantly improve walking speed (MD: − 0.02, 95% CI, − 0.09 to 0.06, p=0.45), nor did it improve walking capacity (MD: 16.28, 95% CI, -26.27 to 58.82, p=0.05), FIM score, WISCI, LEMS, and balance. Similarly, BWSTT combined FES/ES and the control group showed no statistically significant differences in walking speed or capacity.BWSTT, whether used alone or in combination with FES/ES, does not provide a statistically significant advantage over other forms of physical rehabilitation for improving walking function, speed, capacity, balance, or functional independence in people with iSCI.In frühere Studien zum körpergewichtsgestützten Laufbandtraining (body-weight supported treadmill training, BWSTT) bei Rückenmarksverletzungen konnten mögliche Vorteile insbesondere in Hinblick auf eine Verbesserung der Gehfähigkeit aufgezeigt werden. Da allerdings ein Großteil der Evidence aus kleinen Studien stammt, ist ein systematisches Review zur Beurteilung der Gesamtwirkung und Akzeptanz von BWSTT erforderlich. Ziel der vorliegenden Übersichtsarbeit ist es, die Evidence zum Einfluss von BWSTT mit oder ohne Elektrostimulation (funktionelle ES [FES] oder ES) auf die Gehfähigkeit bei Personen mit inkompletten Rückenmarksverletzungen im Vergleich zum „Overground“-Gangtraining oder herkömmlicher Physiotherapie zu untersuchen und quantitativ zusammenzufassen. Es erfolgte eine eingehende Literaturrecherche nach klinischen Studien mit Erwachsenen mit traumatischen Rückenmarksverletzungen (AISA Impairment Scale B, C oder D), in denen BWSTT mit oder ohne Elektrostimulation und „Overground“-Gangtraining oder herkömmlicher Physiotherapie verglichen wurden. Die untersuchten Outcomes waren Gehfunktion (Gehgeschwindigkeit und -kapazität) und funktionelle Unabhängigkeit. BWSTT mit FES/ES wurde unabhängig analysiert und die Daten der einzelnen Studien wurden zur Berechnung der mittleren Unterschiede zwischen den Gruppen mittels eines Random-Effects-/Fixed-Effects-Modells zusammengefasst. Es wurden zwölf randomisierte kontrollierte Studien (RCTs) für die qualitative Synthese und neun Studien für die quantitative Datenanalyse einbezogen. BWSTT als ein Ansatz zur Verbesserung der Gehfähigkeit von Personen mit inkompletten Rückenmarksverletzung konnte weder die Gehgeschwindigkeit signifikant steigern (MD: − 0,02, 95-%-KI: − 0,09–0,06; p=0,45) noch eine Verbesserung von Gehkapazität (MD: 16,28, 95-%-KI: − 26,27–58,82; p=0,05), FIM-Score, WISCI, LEMS und Gleichgewicht herbeiführen. Ebenso fand sich für BWSTT mit oder ohne Elektrostimulation und die Kontrollgruppe kein signifikanter Unterschied hinsichtlich Gehgeschwindigkeit und Gehkapazität.BWSTT bietet bei Personen mit inkompletten Rückenmarksverletzungen weder allein noch kombiniert mit FES/ES einen statistisch signifikanten Vorteil gegenüber anderen Formen der physikalischen Rehabilitation zur Verbesserung der Gehfunktion, Gehgeschwindigkeit, Gehkapazität, des Gleichgewichts oder der funktionellen Unabhängigkeit.
Keywords: spinal cord injury (SCI); rehabilitation; locomotor training; electrical stimulation; body weight supported treadmill training; systematic review